The Reconditioning Growth and Production of Chili Through The Banana Hump and Mimba Leaf Extract - Oktavianus Lumban Tobing; Yanyan Mulyaningsih (Universitas Djuanda, 2020)
The growth regulators of gibberellin and cytokinins are found in banana hump extract, while natural pesticides are found in the neem leaf extract. These two active ingredients can condition the growth and yield of chilies. There have not been any publications on the use of banana hump extracts and neem leaves to increase the growth and production of chili plants. The writing of this research article aims to explore the diversity of Indonesia's biological resources, among others, sword stalk banana hump extract and neem leaves which can stimulate the growth and yield of red chilies. Data analysis used a randomized block design with two variables and 3 repetitions. The first treatment used banana hump extract which consisted of four percentage levels, namely zero, fifteen, thirty, and forty-five percent, and the second treatment used neem leaf extract which consisted of four percentage levels, namely zero, fifteen, thirty, and forty-five, percent. A total of 600 grams of banana hump granules and neem leaves plus 1 liter of methanol, concentrated to a volume of 250 ml were used in this study. The results of the research showed that giving banana hump extract and neem leaves was able to stimulate the growth of leaf area so that it had an impact on increasing photosynthesis and plant metabolism. Fruit weight cannot be stimulated because, during the study, there was a long dry season, so there was a water deficit which was a limiting factor in the production of fruit formation.